Athena Itonia - Lalonde, Gerald V. (Religions in the Graeco-Roman World Ser, 2019)
Intro -- Contents -- Acknowledgements -- Maps and Figures -- Abbreviations -- Introduction -- Chapter 1 Thessaly -- 1 The Thessalian Precedence of Athena Itonia -- 2 The Military Character of Athena Itonia in Thessaly -- 3 The Itonian Cult in the Political and Military Traditions of Thessaly -- 4 The Geography and Archaeology of the Thessalian Cult of Athena Itonia -- 4.1 Introduction -- 4.2 Achaia Phthiotis -- 4.2.1 Itonos -- 4.3 Thessaliotis -- 4.3.1 Modern Philia -- 4.4 Histiaiotis -- 4.4.1 Near Pharkadon -- 4.5 Pelasgiotis -- 4.5.1 Between Pherai and Larisa -- 4.5.2 Krannon -- 4.6 Conclusion -- Chapter 2 Boiotia -- 1 Introduction -- 2 Source, Chronology, and Circumstances of the Establishment of the Itonian Cult in Boiotia -- 3 The Question of Identification of the Itonian Sanctuary near Koroneia -- 3.1 Ancient Testimonia -- 3.2 Modern Topography and Archaeology -- 4 Relation of Other Boiotian Sanctuaries of Athena to the Itoneion near Koroneia -- 5 The Character of Boiotian Athena Itonia and Her Cult -- 6 Iodama -- 7 Functions of the Boiotian Itoneion -- 7.1 Introduction -- 7.2 General Use of the Itoneion -- 7.3 The Boiotian League's General Relations with the Itoneion -- 7.4 The Pamboiotia -- Chapter 3 Athens -- 1 Introduction -- 2 The Epigraphic Evidence -- 3 Location of the Sanctuary of Athena Itonia at Athens -- 4 Origins of The Itonian Cult at Athens: Chronology and Circumstances -- 5 Summary -- Chapter 4 Amorgos -- 1 Introduction -- 2 The Source of the Itonian Cult on Amorgos -- 3 Archons for the Itonia -- 4 Functions of the Honored Archons -- 5 Rituals of the Itonia on Amorgos -- 6 Archontic Monetary Contributions and the Finance of the Itonia -- 7 Honors for the Archons for the Itonia -- 8 Itonian Sanctuary and Festival: Were They Shared by Arkesine and Minoa? -- 9 Facilities Related to the Itonian Festival.